2004
DOI: 10.1007/s00125-003-1311-5
|View full text |Cite
|
Sign up to set email alerts
|

Sustained cardiomyocyte apoptosis and left ventricular remodelling after myocardial infarction in experimental diabetes

Abstract: Aims/hypothesis. Diabetes is known to reduce survival after myocardial infarction. Our aim was to examine whether diabetes is associated with enhanced cardiomyocyte apoptosis and thus interferes with the post-infarction remodelling process in myocardium in rat. Methods. Four weeks after intravenous streptozotocin (diabetic groups) or citrate buffer (controls) injection, myocardial infarction was produced by ligation of left descending coronary artery. Level of cardiomyocyte apoptosis was quantified by TUNEL an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 23 publications
2
36
1
1
Order By: Relevance
“…STZ administration, the number of apoptotic cardiomyocytes was equally high in diabetic and nondiabetic rats 1 week after induction of permanent coronary occlusion. However, at 12 weeks after infarction the number of apoptotic cells was higher in the diabetic compared with the nondiabetic rats both in the border zone of infarction and in the noninfarcted area (Bä cklund et al, 2004).…”
Section: Ischemia/reperfusion Injury In Diabetesmentioning
confidence: 75%
“…STZ administration, the number of apoptotic cardiomyocytes was equally high in diabetic and nondiabetic rats 1 week after induction of permanent coronary occlusion. However, at 12 weeks after infarction the number of apoptotic cells was higher in the diabetic compared with the nondiabetic rats both in the border zone of infarction and in the noninfarcted area (Bä cklund et al, 2004).…”
Section: Ischemia/reperfusion Injury In Diabetesmentioning
confidence: 75%
“…CASP3 is a member of the caspase family and has been recognized as an important initiator and promoter of apoptosis. Enhanced apoptosis of cardiomyocytes has been noted after myocardial infarction in experimental diabetes; an increase in CASP3 levels after infarction interfered with the remodeling process in the myocardium of rats (Bäcklund et al, 2004). Diabetes was found to be associated with enhanced apoptosis and necrosis in both ischemic and nonischemic human myocardia, an adverse effect that is mediated, at least in part, by CASP3 (Chowdhry et al, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, it has been reported that the mortality of myocardial infarction in diabetic patients is more than double that of non-diabetic patients [27]. It appears that cardiac myocytes in the diabetic myocardium are more susceptible to apoptosis [25], suggesting that the higher sensitivity to MI is due to a higher loss of cardiac myocytes via apoptosis in response to the stress [28]. Also, Kuethe et al [29] found that diabetic patients with dilated cardiomyopathy had significantly more apoptotic cells in the heart compared to patients without diabetes.…”
Section: Evidence Of Apoptosis In Cardiovascular Diseasesmentioning
confidence: 96%